Impact of Academic interventions on Students Performance in Electives - Arshia Samin Naqvi; Abbas Zafar (ziauddin University, 2024)
Background: Elective clinical rotations have become a significant part of most of the medical educational curricula. Evaluation of electives is imperative to assess their usefulness in achieving the objective of improving the competencies of graduating students. Results of these evaluations can be used to guide future academic developments. Objective: The purpose of this study was to assess the change in the performance of medical students after academic intervention based on the results of evaluation of previous year electives. Methods: Students' performances in elective rotations were evaluated in the year 2012 and again in 2013 after bringing modifications in teaching / learning program. The data collected was from 60 students. Students consisted of two sets, those who completed their electives in the country while the other completed their electives abroad. Scores were calculated in three distinct domains of education i.e knowledge, attitude and ethical behavior. Independent Sample T test was applied to compare the scores. Results: Findings suggest that as a result of the academic interventions carried out in 2013 in the educational program by the combined efforts of the faculty and students, the scores for all the three educational domains in both the local and abroad groups improved considerably. Conclusion: Study findings conclude that active curricular interventions play important role in improving the outcomes of teaching programs. KEY WORDS: Knowledge, attitude, participatory action research, ethical behavior